Neuronal Transdifferentiation Potential of Human Mesenchymal Stem Cells from Neonatal and Adult Sources by a Small Molecule Cocktail - Lorena V. Cortés-Medina; Herminia Pasantes-Morales; Alejandro Aguilera-Castrejon; Arturo Picones; Cesar O. Lara-Figueroa; Enoch Luis; Juan Jose Montesinos; Victor A. Cortés-Morales; M. P. De la Rosa Ruiz; Erika Hernández-Estévez; Laura C. Bonifaz; Marco Antonio Alvarez-Perez; et al. (Hindawi Limited, 2019)
Human mesenchymal stem cells (MSCs) are good candidates for brain cell replacement strategies and have already been used as adjuvant treatments in neurological disorders. MSCs can be obtained from many different sources, and the present study compares the potential of neuronal transdifferentiation in MSCs from adult and neonatal sources (Wharton's jelly (WhJ), dental pulp (DP), periodontal ligament (PDL), gingival tissue (GT), dermis (SK), placenta (PLAC), and umbilical cord blood (UCB)) with a protocol previously tested in bone marrow- (BM-) MSCs consisting of a cocktail of six small molecules: I-BET151, CHIR99021, forskolin, RepSox, Y-27632, and dbcAMP (ICFRYA). Neuronal morphology and the presence of cells positive for neuronal markers (TUJ1 and MAP2) were considered attributes of neuronal induction. The ICFRYA cocktail did not induce neuronal features in WhJ-MSCs, and these features were only partial in the MSCs from dental tissues, SK-MSCs, and PLAC-MSCs. The best response was found in UCB-MSCs, which was comparable to the response of BM-MSCs. The addition of neurotrophic factors to the ICFRYA cocktail significantly increased the number of cells with complex neuron-like morphology and increased the number of cells positive for mature neuronal markers in BM- and UCB-MSCs. The neuronal cells generated from UCB-MSCs and BM-MSCs showed increased reactivity of the neuronal genes TUJ1, MAP2, NF-H, NCAM, ND1, TAU, ENO2, GABA, and NeuN as well as down- and upregulation of MSC and neuronal genes, respectively. The present study showed marked differences between the MSCs from different sources in response to the transdifferentiation protocol used here. These results may contribute to identifying the best source of MSCs for potential cell replacement therapies.